Primary Lung Dendritic Cell Cultures to Assess Efficacy of Spectinamide-1599 Against Intracellular Mycobacterium tuberculosis - Santos, Karen; Lukka, Pradeep B.; Grzegorzewicz, Anne; Jackson, Mary; Trivedi, Ashit; Pavan, Fernando; Chorilli, Marlus; Braunstein, Miriam; Hickey, Anthony; Meibohm, Bernd; Gonzalez-Juarrero, Mercedes (Frontiers in Microbiology, 2018)
There is an urgent need to treat tuberculosis (TB) quickly, effectively and without side effects. Mycobacterium tuberculosis (Mtb), the causative organism of TB, can survive for long periods of time within macrophages and dendritic cells and these intracellular bacilli are difficult to eliminate with current drug regimens. It is well established that Mtb responds differentially to drug treatment depending on its extracellular and intracellular location and replicative state. In this study, we isolated and cultured lung derived dendritic cells to be used as a screening system for drug efficacy against intracellular mycobacteria. Using mono- or combination drug treatments, we studied the action of spectinamide-1599 and pyrazinamide (antibiotics targeting slow-growing bacilli) in killing bacilli located within lung derived dendritic cells. Furthermore, because IFN-γ is an essential cytokine produced in response to Mtb infection and present during TB chemotherapy, we also assessed the efficacy of these drugs in the presence and absence of IFN-γ. Our results demonstrated that monotherapy with either spectinamide-1599 or pyrazinamide can reduce intracellular bacilli burden and that there is a very strong synergistic effect only if both drugs are administered simultaneously with IFN-γ. Thus, while it is not uncommon for the effects of drugs to be tested on intracellular Mtb in macrophages, this is not routinely carried out with Mtb in dendritic cells. Here we developed such a system and used it to evaluate spectinamide1599 and pyrazinamide intracellular efficacy against Mtb.